Evaluation of free or anchored antimicrobial peptides as candidates for the prevention of orthopaedic device‐related infections. (14th July 2017) - D'Este, Francesca; Oro, Debora; Boix‐Lemonche, Gerard; Tossi, Alessandro; Skerlavaj, Barbara
Abstract : The prevention of implant‐associated infection, one the most feared complications in orthopaedic surgery, remains a major clinical challenge and urges development of effective methods to prevent bacterial colonization of implanted devices. Alpha‐helical antimicrobial peptides (AMPs) may be promising candidates in this respect due to their potent and broad‐spectrum antimicrobial activity, their low tendency to elicit resistance and possible retention of efficacy in the immobilized state. The aim of this study was to evaluate the potential of five different helical AMPs, the cathelicidins BMAP‐27 and BMAP‐28, their (1–18) fragments and the rationally designed, artificial P19(9/G7) peptide, for the prevention of orthopaedic implant infections. Peptides were effective at micromolar concentrations against 22 Staphylococcus and Streptococcus isolates from orthopaedic infections, while only BMAP‐28 and to a lesser extent BMAP‐27 were active against Enterococcus faecalis . Peptides in solution showed activities comparable to those of cefazolin and linezolid, on a molar basis, and also a variable capacity to neutralize bacterial lipopolysaccharide, while devoid of adverse effects on MG‐63 osteoblast cells at concentrations corresponding to the MIC. The (1–18) BMAP fragments and P19(9/G7) were selected for further examination, based on better selectivity indices, and showed effectiveness in the presence of hyaluronic acid and in synovial fluid, while human serum affected their activity to variable extents, with BMAP‐27(1–18) best retaining activity. This peptide was immobilized on streptavidin–resin beads and retained activity against reference Staphylococcus epidermidis and Staphylococcus aureus strains, with negligible toxicity towards osteoblasts, underlining its potential for the development of infection‐resistant biomaterials for orthopaedic application. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Peptide structure adapted from PDB solution structure 2KET (BMAP‐27).